2015
DOI: 10.1002/ajoc.201500274
|View full text |Cite
|
Sign up to set email alerts
|

A Route to 1‐Alkenylphosphine Derivatives via the Zr‐Catalyzed Reaction of 1‐Alkynylphosphines with Triethylaluminum

Abstract: The Cp2ZrCl2‐catalyzed reaction of 1‐alkynyldiphenylphosphines with Et3Al, followed by deuterolysis and oxidation, affords substituted (E)‐(but‐1‐en‐1‐yl‐1,4‐d2)diphenylphosphine oxides. It is suggested that the reaction proceeds through the formation of intermediate aluminacyclopent‐2‐enes. Substituted (E)‐but‐1‐en‐1‐yldiphenylphosphine sulfides and 4‐butyl‐5‐(diphenylphosphoryl)‐1‐phenyl‐2,3‐dihydrophosphole 1‐oxide were prepared by reacting intermediate organoaluminum compounds with S8 and PhPCl2. The mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…strates that αor β-heteroatom-substituted alkynes react much more promptly than internal aliphatic alkynes, and thus enhances significantly the synthetic scope of the transformation by disclosing an efficient access to some heteroatom-functionalized alkenes with control of the double-bond geometry. The study represents an improvement over previous works on Zr-catalyzed cycloalumination of propargylamines 21 and alkynylphosphines 22 because the current catalytic system consisting of Et 2 Zn, Ti(O-iPr) 4 , and EtMgBr is more practical and less costly. Moreover, the dizincated species offer more potential for subsequent functionalization than the dialuminated species.…”
Section: Letter Syn Lettmentioning
confidence: 93%
See 1 more Smart Citation
“…strates that αor β-heteroatom-substituted alkynes react much more promptly than internal aliphatic alkynes, and thus enhances significantly the synthetic scope of the transformation by disclosing an efficient access to some heteroatom-functionalized alkenes with control of the double-bond geometry. The study represents an improvement over previous works on Zr-catalyzed cycloalumination of propargylamines 21 and alkynylphosphines 22 because the current catalytic system consisting of Et 2 Zn, Ti(O-iPr) 4 , and EtMgBr is more practical and less costly. Moreover, the dizincated species offer more potential for subsequent functionalization than the dialuminated species.…”
Section: Letter Syn Lettmentioning
confidence: 93%
“…Meanwhile, it is known that 1-alkynylphosphines, 1-alkynylphosphonates, propargylamines, 1-alkynyl selenides, and 1-alkynyl sulfides are efficient substrates for the preparation of zirconacyclopentenes [17][18][19][20] and aluminacyclopentenes. [21][22][23][24] Regarding 2-zincoethylzincation, only one case of the preparation of organozinc derivative in 63% yield only after 4 days using the Ti-Mg-catalyzed reaction of 5decyne with Et 2 Zn has been reported in the literature. 25 However, this reaction is a unique example of carbozincation of the triple carbon-carbon bond with Et 2 Zn using oxidative coupling of ethylene and 5-decyne on titanium(II) in catalytic cycle.…”
mentioning
confidence: 99%
“…46 Generally, it is consistent with our earlier views about the key role of zirconocene-ethylene intermediate in this reaction. 47 While considering the Zr-catalyzed reaction of Et 3 Al with propargyl alcohols, propargylamines, 37 and 1-alkynylphosphines, 38 we suggested that the Et 2 AlCl molecule located in the zirconacyclopropene coordination sphere is the principal factor determining the regioselectivity of cycloalumination. Similarly, in the case of cycloalumination of 1-alkynyl selenides, one can assume the formation of stable five-membered cyclic complex (Scheme 2).…”
Section: Scheme 1 Zr-catalyzed сYcloalumination Of 1-alkynyl Selenidementioning
confidence: 98%
“…35,36 As an alternative, recently we developed regio-and stereoselective methods for the preparation of О-, N-, and P-containing alkenes by Cp 2 ZrCl 2catalyzed cycloalumination of propargyl and homopropargyl alcohols, propargylamines, 37 and 1-alkynylphosphines. 38 The efficiency of carboalumination for the synthesis of P-and S-containing alkenes was demonstrated by Cp 2 ZrCl 2 -catalyzed ethylalumination of 1-alkynyl phosphorus oxides 39 and methylalumination of alkynyl sulfones, sulfoxides, and sulfides. 40 Thus, carboalumination of alkynes is an efficient method for the synthesis of various functionally substituted alkenes.…”
mentioning
confidence: 99%
“…1 Previously, we developed methods for the preparation of 1-alkenyl phosphines and phosphine oxides based on Zr-catalyzed carboalumination of 1-alkynyl phosphines and phosphine oxides. 2,3 It has been found that the pathway of the reaction of 1-alkynyl phosphine derivatives with organoaluminum compounds strongly depends on the nature of the substrate and the solvent. The ethylalumination takes place under the action of Et 3 Al in the case of 1-alkynyl phosphines and phosphine oxides in hexane as the solvent.…”
mentioning
confidence: 99%